US Foreign Policy Towards Iraq from 2017 to 2025 - Suleiman, Amin Jundi Suleiman; Mahmud, Prof.Dr. Rebwar Karim Mahmud (Sulaimani Journal for Humanities, 2025)
U.S. foreign policy toward the Middle East in general, and Iraq in particular, has witnessed fundamental changes and transformations influenced by the strategies and orientations of various administrations, particularly after the events of September 11, 2001, which were the primary motivation for the outbreak of the war against the Taliban in Afghanistan (2001-2021), and the war against Iraq in 2003. These events and wars produced radical changes in U.S. foreign policy, not only toward the Middle East, but also toward the entire world, beginning with George W. Bush's assumption of the US presidency (2001-2009). The decision to wage war against Iraq in 2003, lacked international legitimacy, and occupying it was one of the most significant of these changes in U.S. foreign policy. Therefore, the Barack Obama administration (2009-2017) insisted on ending the war and withdrawing US forces from Iraq in 2011 under the Strategic Framework Agreement. However, in 2014, US forces returned to confront ISIS terrorist organization. In the same context, the foreign policy of the first Donald Trump administration (2017-2021) emphasized the withdrawal of U.S. forces from Iraq, but decided to kill General Qassem Soleimani, commander of the Quds Force of the Iranian Revolutionary Guard Corps, near Baghdad International Airport in 2020. This incident sparked a new and acute crisis in relations between the United States and Iraq, on the one hand, and between it and Iran, on the other, and made Iraq, once again, an arena of conflict and confrontation between them.
Keywords: US Foreign Policy; Iraq; Coalition Against ISIS